2021
DOI: 10.1038/s41598-021-98220-4
|View full text |Cite
|
Sign up to set email alerts
|

On the function of biosynthesized cellulose as barrier against bacterial colonization of VAD drivelines

Abstract: Bacterial colonization of drivelines represents a major adverse event in the implantation of left ventricular assist devices (L-VADs) for the treatment of congestive heart failure. From the external driveline interface and through the skin breach, pathogens can ascend to the pump pocket, endangering the device function and the patient’s life. Surface Micro-Engineered Biosynthesized cellulose (BC) is an implantable biomaterial, which minimizes fibrotic tissue deposition and promotes healthy tissue regeneration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In a small study, merbromin used for local irrigation showed a significant reduction in the development of infection, with all 31 patients treated being free of infection after LVAD implantation [ 81 ]. Other approaches, such as wrapping the silicone driveline with biosynthesized cellulose, have shown a reduction in local bacterial colonization, which, together with the known anti-fibrotic effect of biosynthesized cellulose, may promote more efficient immune clearance after driveline implantation and support the efficacy of local antibiotic treatments [ 82 ].…”
Section: Complications Associated With Bridge To Transplant Lvad Therapymentioning
confidence: 99%
“…In a small study, merbromin used for local irrigation showed a significant reduction in the development of infection, with all 31 patients treated being free of infection after LVAD implantation [ 81 ]. Other approaches, such as wrapping the silicone driveline with biosynthesized cellulose, have shown a reduction in local bacterial colonization, which, together with the known anti-fibrotic effect of biosynthesized cellulose, may promote more efficient immune clearance after driveline implantation and support the efficacy of local antibiotic treatments [ 82 ].…”
Section: Complications Associated With Bridge To Transplant Lvad Therapymentioning
confidence: 99%
“…As a gel-like product, for instance, it soothes the skin and does not engraft with the skin. A recent study just reported the promising results of BC as a biomaterial implant, in which BC was tested as a cardiac implant to mimic the function as a left ventricular assist device for the treatment of congestive heart failure [ 16 ]. Recent drug delivery research has further demonstrated various other advantages of BC, including its promising effects on controlling drug release, biocompatibility, low immunogenicity and ease of production/handling.…”
Section: Introductionmentioning
confidence: 99%